2018
DOI: 10.1161/str.0000000000000159
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Dysphagia Screening Strategies on Clinical Outcomes After Stroke: A Systematic Review for the 2018 Guidelines for the Early Management of Patients With Acute Ischemic Stroke

Abstract: Introduction— Dysphagia screening protocols have been recommended to identify patients at risk for aspiration. The American Heart Association convened an evidence review committee to systematically review evidence for the effectiveness of dysphagia screening protocols to reduce the risk of pneumonia, death, or dependency after stroke. Methods— The Medline, Embase, and Cochrane databases were searched on November 1, 2016, to identify randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 17 publications
5
45
0
1
Order By: Relevance
“…SAP occurred in 13.6% of patients [95% confidence interval (CI), 8. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].9%] at a median time of 3 days after stroke (IQR, 2-4) and there was no difference in its occurrence between the pre-GUSS and GUSS periods (12.5% vs. 15.1%, P = 0.490). The characteristics of patients according to the occurrence of SAP are described in Table S1.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…SAP occurred in 13.6% of patients [95% confidence interval (CI), 8. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].9%] at a median time of 3 days after stroke (IQR, 2-4) and there was no difference in its occurrence between the pre-GUSS and GUSS periods (12.5% vs. 15.1%, P = 0.490). The characteristics of patients according to the occurrence of SAP are described in Table S1.…”
Section: Resultsmentioning
confidence: 96%
“…Among the final population of patients (n = 344), 204 were admitted during the pre-GUSS period and 140 during the GUSS period. Median age was 71 years (IQR, 59-79), 178 were male (51.7%) and median National Institutes of Health Stroke Scale score was 11 (IQR, [6][7][8][9][10][11][12][13][14][15][16][17][18]. Baseline characteristics of the study population according to the inclusion period are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A recently published review found insufficient evidence to determine the effect of DSP [39]. However Smith et al [39] included only randomized controlled trials and did not focus specifically on pneumonia as an outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However Smith et al [39] included only randomized controlled trials and did not focus specifically on pneumonia as an outcome. Our review found emerging evidence that EDS is associated with lower incidence of SAP and supports current guidelines that all patients should be screened for dysphagia on admission before oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…Of 216 patients with a nothing‐by‐mouth status, 13.9% still developed pneumonia. A systematic review concluded that there is insufficient evidence that current dysphagia screening protocols reduce risk for pneumonia, death, or dependency after stroke . Therefore, ideally, bedside screening measures should lead to supplemental evaluation with instrumental assessment for a comprehensive, thorough examination of oropharyngeal anatomy and physiology, as indicated and available.…”
Section: Screening and Evaluationmentioning
confidence: 99%